MULTICRITERIA ASSESSMENT OF THE EFFICIENCY OF TRANSPORT AND CUSTOMS INFRASTRUCTURE FACILITIES - Luzhanska, Nataliia (Proceedings of National Aviation University (archive), 2019)
The article proposes the approach regarding the multicriteria assessment of the efficiency of transport and customs infrastructure facilities by comparing the objects under examination with the benchmark. The object of the research is the process of multicriteria efficiency assessment of freight customs complexes operation. The purpose of the work is the development of theoretical foundations and a comprehensive efficiency assessment of transport and customs infrastructure facilities. The research method is the multicriteria assessment of transport and customs infrastructure facilities. A significant number of transport and customs infrastructure facilities and criteria for their functioning, the need to assess the effectiveness of the fiscal service in general as well as of individual facilities naturally require the use of mathematical apparatus for assessing the effectiveness of management and state regulation of the processes of cargo transportation across the customs border. The peculiarities of operation of transport and customs infrastructure facilities require unification of project decisions regarding the operation of transport and customs infrastructure facilities, their capacity, size, technical, technological and organizational support. The peculiarities of determining the efficiency of transport and customs infrastructure facilities, depending on the specifics of their operation, include: the dependence of the value of their performance indicators on the form of ownership of the subject to assessment; inconsistencies in the local criteria characterizing customs infrastructure facilities; heterogeneity and incompatibility of local criteria not only in relation to each other, but also with respect to the integral efficiency indicator peculiar to customs infrastructure facilities; the need for cost accounting of the forced unification of design decisions on customs infrastructure facilities. The results of the article can be implemented in logistics intermediaries` activities when performing foreign trade operations. Possible assumptions on the further development of the research object are elaborating a methodology for evaluating the activity of transport and customs infrastructure facilities.